64.4k views
3 votes
Factor 2x^2-9x+9=0 and please show ur steps

User Kurumkan
by
4.6k points

1 Answer

2 votes

Answer:

♡ hi there, madi here! ♡

hope your having a great day.

I did the math so here's your answer.

2x−3)(x−3)=0

If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.

2x-3=0. x-3=0

Set the first factor equal to 0 and solve.

x=3/2

Set the next factor equal to 0 and solve.

x=3

Therefore, the final solution is all the values that make (2x-3) (x-3)=0 true. x=3/2,3♡

✧・゚: *✧・゚:・゚✧*:・゚✧・゚: *✧・゚:・゚✧*:・゚✧

User Peter Brennan
by
6.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.